2008
DOI: 10.1111/j.1468-0297.2007.02127.x
|View full text |Cite
|
Sign up to set email alerts
|

Financial Innovation, Macroeconomic Stability and Systemic Crises

Abstract: We present a general equilibrium model of intermediation designed to capture some of the key features of the modern financial system. The model incorporates financial constraints and state-contingent contracts, and contains a clearly defined pecuniary externality associated with asset fire sales during periods of stress. If a sufficiently severe shock occurs during a credit expansion, this externality is capable of generating a systemic financial crisis that may be self-fulfilling. Our model suggests that fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
19

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 46 publications
0
27
0
19
Order By: Relevance
“…9 For simplicity, I assume that the commitment problem is extreme (that is, banks cannot commit to pay any fraction of their production to global investors). Assuming a milder but sufficiently strong commitment problem where banks can commit a small fraction of their production, as in Lorenzoni (2008) and Gai et al (2008), does not change the results of this paper. On the other hand, if we complete the markets by allowing banks to borrow from global investors by pledging the future return stream from the assets, there would not be a reason for fire sales and the first best world would be established.…”
Section: Modelmentioning
confidence: 79%
See 3 more Smart Citations
“…9 For simplicity, I assume that the commitment problem is extreme (that is, banks cannot commit to pay any fraction of their production to global investors). Assuming a milder but sufficiently strong commitment problem where banks can commit a small fraction of their production, as in Lorenzoni (2008) and Gai et al (2008), does not change the results of this paper. On the other hand, if we complete the markets by allowing banks to borrow from global investors by pledging the future return stream from the assets, there would not be a reason for fire sales and the first best world would be established.…”
Section: Modelmentioning
confidence: 79%
“…In my model, fire sales result from the combined effect of asset specificity and correlated shocks that hit an entire industry or economy. This idea, which originated in Williamson (1988) and Shleifer and Vishny (1992), was later employed by Lorenzoni (2008), Gai et al (2008), Korinek (2011), andStein (2012). These latter papers show that under the pecuniary externalities that arise from asset fire sales, there exists an inefficiently high level of borrowing and hence investment in risky assets in the decentralized equilibrium.…”
Section: Literature Reviewmentioning
confidence: 95%
See 2 more Smart Citations
“…Although individual countries and the international organizations, particularly the BIS, were well aware of the need to consider aggregate issues and the importance of correlated risks and herding the balance of emphasis has been shown to be firmly wrong (Turner 2009). The Bank of England (Gai et al 2006(Gai et al , 2007(Gai et al , 2008 had already identified that banks underprovided for the systemic consequences of their risks, that their behaviour would tend to amplify shocks and that the increased macroeconomic stability was likely to reduce the chance of crises but increase the severity of any that did occur. However, the crisis hit before this work was fully developed and the stress tests intended could alter the preparedness of either Bank of England or the individual banks.…”
mentioning
confidence: 98%